First evidence of protein modulation by polystyrene microplastics in a freshwater biological model. (July 2019) - Magni, S.; Della Torre, C.; Garrone, G.; D'Amato, A.; Parenti, C.C.; Binelli, A.
Abstract: Microplastics (MPs) are now one of the major environmental problems due to the large amount released in aquatic and terrestrial ecosystems, as well as their diffuse sources and potential impacts on organisms and human health. Still the molecular and cellular targets of microplastics' toxicity have not yet been identified and their mechanism of actions in aquatic organisms are largely unknown. In order to partially fill this gap, we used a mass spectrometry based functional proteomics to evaluate the modulation of protein profiling in zebra mussel ( Dreissena polymorpha ), one of the most useful freshwater biological model. Mussels were exposed for 6 days in static conditions to two different microplastic mixtures, composed by two types of virgin polystyrene microbeads (size = 1 and 10 μm) each one. The mixture at the lowest concentration contained 5 × 105 MP/L of 1 μm and 5 × 105 MP/L of 10 μm, while the higher one was arranged with 2 × 106 MP/L of 1 μm and 2 × 106 MP/L of 10 μm. Proteomics' analyses of gills showed the complete lack of proteins' modulation after the exposure to the low-concentrated mixture, while even 78 proteins were differentially modulated after the exposure to the high-concentrated one, suggesting the presence of an effect-threshold. The modulated proteins belong to 5 different classes mainly involved in the structure and function of ribosomes, energy metabolism, cellular trafficking, RNA-binding and cytoskeleton, all related to the response against the oxidative stress. Graphical abstract: Image 105 Highlights: Effect of polystyrene microplastics on protein regulation of a freshwater organism. The highest microplastic concentration modulated 78 different proteins. The most modulated proteins are involved in the response against oxidative stress. Abstract : a mixture of polystyrene microplastics (2 × 10 6  MP/L of 1 μm and 2 × 10 6  MP/L of 10 μm) was able to modulate 78 different proteins of the zebra mussels' gills most involved in the oxidative stress response.